Are early adopters willing to accept frozen, ready‐to‐cook mealworms as a food source?. Issue 5 (30th June 2022) - Rovai, Dominic; Amin, Samir; Lesniauskas, Ruta; Wilke, Kristine; Garza, Jeff; Lammert, Amy
Abstract: Literature suggests that edible insects are most likely to be accepted when they are presented in the nonvisible form, but is it the only way? This research examines the acceptability of whole, ready‐to‐cook mealworms among early adopters. An online questionnaire was developed and distributed without restriction via email, social media (Facebook) and in‐person referrals. Participants were assigned to predetermined clusters based on their willingness to adopt insects ( n = 85 No‐thank‐you's, n = 85 Hideaways, n = 53 Daredevils, and n = 78 Peekaboo's), sent a follow‐up questionnaire which presented a video of frozen, ready‐to‐cook mealworms cooking, and asked their willingness to buy the product. Analysis of variance, Tukey's means comparisons, and principal component analysis maps were used to analyze the data. Early adopters (Daredevils–53% and Peekaboo's–38%), motivated by the novel experience and ease of preparation, would consume frozen, ready‐to‐cook mealworms in a stir‐fry, with vegetables, in a taco/burrito, or with rice. Practical Applications: This work demonstrates the value of segmentation of consumers. By narrowing the target audience, this work suggests that frozen, ready‐to‐cook mealworms may be a viable product form for a niche segment of consumers. The adoption of mealworms in this form may be beneficial for entomophagy as a whole by increasing exposure and familiarity of insects as a food source. Potential benefits of this research include future product development and consumer evaluation opportunities to help better understand how to develop a product that consumers are willing to purchase in use as a substitute for traditional livestock proteins. Incremental shifts to purchasing edible insects in place of traditional livestock protein will have a positive sustainable impact on the food supply.